Human Health Risk Assessment of Heavy Metals Bioaccumulation In Fish and Mussels from Jakarta Bay - Ajeng Kurniasari Putri; Giri Rohmad Barokah; Nuri Andarwulan (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2017)
Aquatic environment of Jakarta Bay have already been highlighted due to its heavy metals contamination which may lead into food safety concern of fisheries products derived from this region. This research aimed to investigate bioaccumulation level of heavy metals (Pb, Cd, and As) in fish and mussels from Jakarta Bay, as a human risk assessment of seafood consumption. Samples of mussels and fish were taken from Penjaringan, Tarumanegara, Cilincing, and Tanjung Pasir district. Bioaccumulation of heavy metals was analyzed by Inductively Coupled Plasma -Mass Spectrometry technique. Results of the study revealed that metals bioaccumulation in fisheries products were varied, with As (Arsenic) as the highest metal contaminant (0.68 mg/kg, dry weight). Furthermore, estimated daily intake (EDI), target hazard quotient (THQ), total target hazard quotient (TTHQ), and safety limits prescribed by various agencies, showed that consumption of fisheries products from Jakarta Bay considered as relatively safe for human health in total of food ingestion rate of fish 57.34 g/day. These results are expected to serve as a baseline to construct preventive and palliative policies for food safety of fisheries products from Jakarta Bay.